Construction of the "Secondary Distribution" Indicator System of Family Doctor Team Performance Based on Contracted Service Fee - GAO Xiang, CHEN Hong, ZHOU Rong, SHI Jianwei, YU Wenya, LYU Yipeng, ZHOU Liang, WANG Zhaoxin, HUANG Lei (Zhongguo quanke yixue, 2024)
Background The existing family doctor team performance appraisal system is lack of incentive effect, which has hindered the quality development of contracted family doctor services. However, the performance appraisal system based on family doctor teams includes two processes of "primary distribution" and "secondary distribution", which is more capable of mobilizing the work motivation of the family doctor team members. At present, there is a lack of performance evaluation indicator systems for family doctor assistants and public health physicians, although these two groups of people play an important role in the family doctor team. Objective To construct "secondary distribution" indicator system of family doctor team performance based on contracted service fee, with regard to the roles of family doctor assistants and public health physicians. Methods The draft of the "secondary distribution" indicator system of family doctor team performance was preliminarily formulated through literature analysis and semi-structured interview. On the basis of the draft, an expert consultation questionnaire was designed, and two rounds of expert consultation were implemented and completed from October 2021 to April 2022 to develop the "secondary distribution" indicator system of family doctor team performance based on contracted service fee was established. Results The recovery rates of the two rounds of expert consultation questionnaires was 100.0%. For the secondary distribution system of family doctor assistants and public health physicians, the authority coefficient for the first round of correspondence was 0.742 2 and 0.742 0, respectively. Finally, the "secondary distribution" indicator system of family physician assistants, including 3 first-level and 10 second-level indicators, and the "secondary distribution" indicator system of public health physicians, including 3 first-level and 13 second-level indicators, were constructed. Conclusion The final "secondary distribution" indicator system of family physician assistants with 3 primary indicators and 10 secondary indicators and "secondary distribution" indicator system of public health physicians with 3 primary indicators and 13 secondary indicators is logical and scientific to a certain extent, reflecting the labor value of family doctor assistants and public health doctors in the family doctor team in providing contracted services, which is conducive to the special incentive function of contracted service fee and needs to be optimized and improved in the actual assessment in the future.